Information and Psychological Security of Employees of Law Enforcement Agencies and Law Enforcement Agencies: The State and Prospects of Research - Pozdnyakov, V.M.; Petrov, V.E.; Kokurin, A.V. (Sovremennaâ Zarubežnaâ Psihologiâ, 2024)
The article is devoted to the analysis of issues related to ensuring informational and psychological security for members of the security forces and law enforcement agencies. The focus is on such aspects as: ensuring personal security at the level of assimilating patterns of optimal official behavior in working with information; the total informatization of agency activities and the problem of special professional training of employees; the development of informational and psychological security technologies during ongoing hybrid warfare; analysis of the consequences of negative informational and psychological impacts on the personnel of security and law enforcement agencies; and the study of the role of the media and social networks in violating informational and psychological security. The material provides an orientation towards foreign approaches to countering informational threats to employees of security forces and law enforcement agencies. The authors show that informational and psychological counteraction, under the current conditions of Russia's special military operation in Ukraine and the expansion of sanctions, should be doctrinally regulated by the state, not only within security and law enforcement agencies. Prospective research areas identified include: forecasting psychological threats, psychological resilience and security in communication with the population during emergencies, the impact of false information on legal consciousness and interpersonal relations in the law enforcement environment, informational propaganda, and overcoming the deficit (limitations) of information relevant to society. Статья посвящена анализу проблематики обеспечения информационно-психологической безопасности представителей силовых структур и правоохранительных органов. В фокусе внимания были такие аспекты: как обеспечение личной безопасности на уровне усвоенности образцов оптимального должностного поведения в работе с информацией; тотальная информатизация деятельности ведомств и проблема специальной профессиональной подготовки сотрудников; отработка технологий информационно-психологической безопасности при ведущейся гибридной войне; анализ последствий негативного информационно-психологического воздействия на личный состав силовых и правоохранительных ведомств; исследование роли СМИ и соцсетей Интернета в нарушениях информационно-психологической безопасности. Материал позволяет сориентироваться в зарубежных подходах к противодействию информационным угрозам сотрудникам силовых структур и правоохранительных органов. Авторами показывается, что информационно-психологическое контрвоздействие в современных условиях проведения Россией специальной военной операции на Украине и расширения санкций должно быть доктринально регламентировано государством, а не только в силовых и правоохранительных ведомствах. В качестве перспективных исследований выделены: прогнозирование психологических угроз, психологическая устойчивость и безопасность в области коммуникации с населением при чрезвычайной ситуации, влияние недостоверной информации на правосознание и межличностные отношения в правоохранительной среде, информационная пропаганда и преодоление дефицита (ограничения) актуальной для общества информации.